The Influence of Prices, Advertising, and Product Assessment on Purchase Decisions at Shoppe by State High School Students in Cibodas District, Tangerang City - Febri, Ronal; Yulizar, Ismayudin; Muljadi, Muljadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The findings of research conducted using Smart PLS version 4.0 show that, with a path coefficient value of 0.000 for each, product and advertising ratings have a big impact on high school students' decisions to buy on Shopee. Price, however, also has an impact on the decision about what to buy (with a path coefficient value of 0.165), but is not statistically significant. Overall, advertising, product ratings, and price together explained approximately 95.6% of the variation in students' purchasing decisions. These findings provide an important picture of the factors that influence purchasing decisions on Shopee for high school students in Cibodas District, Tangerang City.